Legal analysis of child protection in family matters in Zanzibar : challenges and reforms - Omar Hamdan, Sikujua (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
The study examines the adequacy of the laws in protecting the children rights in Zanzibar. The laws in the current stands are inadequate in providing support for the protection of the well-being of the children. This is due to the discrepancies such as the non-existence of comprehensive family law, non-shariah compliance, outdated laws and conflict of jurisdiction in the application of family laws. The study is limited to maintenance, a legitimacy status of the children, adoption, inheritance and custody of children. It also focuses on the analysis of the conflict between Islamic principles and CRC as adopted by Tanzania in relation to Zanzibar. Apart from that, Islamic law has provided for the rights of the child such as the right to life, dignity, religion, family and property. Islam and CRC are similar in many rights however, some of these rights contradict each other. For instance, freedom of religion, right to family especially in child marriage and custody. Besides, the United Republic of Tanzania adopted CRC without reservation and Zanzibar has to follow the same, as it has no mandate to ratify the international convention by itself. In doing so, Muslims children suffer on the application of the provisions of the laws and protection of family matters as some provisions are non-harmonized. Some of the existing laws on the protection of the children in family matters indicated the need for future reforms. The main methodology used in this research work was, qualitative study whereby the data analysis used to come up with useful conclusions in analyzing the findings. The study mainly analyzed Zanzibar legal frameworks on its inadequacy protection of children rights in family matters. The interviews were employed with selected respondents mostly the policymakers, the legal officers and community members. The study shows that the intensive reform of the laws is required to minimize the violations in the protection of the children as the future generation of Zanzibar.